PENGARUH AKAD PENDANAAN (FUNDING) TERHADAP KEPUASAN NASABAH PADA BANK ACEH SYARIAH CAPEM KOTA JUANG - Syifa Ul Husna (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2023)
Syariah institutions currently have sharia-based products and are in great demand by the public, because people gradually begin to know and realize that syariah funding products have characteristics and concepts that are different from other institutions. With the good quality of a funding product, this will also have a positive impact on customer satisfaction. So in this case the author wants to examine the relationship between good funding and customer satisfaction at Bank Aceh Syariah Capem Kota Juang. The hypotheses in this study are funding contracts and customer satisfaction. Based on the results of research conducted through the data collection stage by distributing questionnaires to 65 customers with various statements and questions and tested using the SPSS version 25 application. It can be concluded that in the t-Test Coefficient table (partial) it can be seen that the value of t counts the funding agreement variable (funding) is 9.673 > 1.998, and the significance value is 0.000 <0.05. then it can be decided that the funding contract variable (X) has a positive effect on customer satisfaction.